1992
DOI: 10.1159/000267168
|View full text |Cite
|
Sign up to set email alerts
|

Ibudilast May Improve Retinal Circulation in Patients with Diabetes mellitus

Abstract: Ibudilast selectively vasodilates cerebral vessels without reducing blood pressure. We investigated the effect of the drug on retinal circulation in 8 patients with diabetes mellitus, using the video-densitometric image analysis of fluorescein angiography. We compared the build up time, the time constant of washout rate and the mean circulation time (MCT) before and after oral therapy with ibudilast. After 2 weeks of daily administration (30 mg), MCT was shortened significantly (4.2 ± 2.8 vs. 3.0 ± 1.6 s, p = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
(17 reference statements)
2
5
0
Order By: Relevance
“…These actions of ibudilast may have a protective effect on the progression of microangiopathy in type 2 DM subjects. Although little is known about the effect of ibudilast on diabetic microangiopathy, the present results were consistent with the report of Suzuki et al [7]or Sone et al [8]. Suzuki et al [7]suggested that ibudilast may be useful for diabetic retinopathy, since it improved retinal circulation in patients with diabetes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These actions of ibudilast may have a protective effect on the progression of microangiopathy in type 2 DM subjects. Although little is known about the effect of ibudilast on diabetic microangiopathy, the present results were consistent with the report of Suzuki et al [7]or Sone et al [8]. Suzuki et al [7]suggested that ibudilast may be useful for diabetic retinopathy, since it improved retinal circulation in patients with diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…Although little is known about the effect of ibudilast on diabetic microangiopathy, the present results were consistent with the report of Suzuki et al [7]or Sone et al [8]. Suzuki et al [7]suggested that ibudilast may be useful for diabetic retinopathy, since it improved retinal circulation in patients with diabetes. Sone et al [8]indicated that ibudilast is effective in ameliorating diabetic microangiopathy and macroangiopathy of the lower limbs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Prior to registration the images were shade-corrected to remove any low-frequency intensity content such as that produced by uneven illumination of the images (Spencer 1992). This is achieved by subtracting a grossly median filtered version of the image from itself, and produces an image in which only small features such as the retinal vessels are present.…”
Section: Registrationmentioning
confidence: 99%
“…21,22) A previous study demonstrated that 2-week administration of ibudilast shortened the mean retinal circulation time in patients with diabetes mellitus. 23) The results suggest that chronic treatment with ibudilast would exert beneficial effects on the retinal circulation. However, the mechanism underlying the effects remains to be established.…”
mentioning
confidence: 95%